Karl Polanyi on Strategy: The Effects of Culture, Morality and Double-Movements on Embedded Strategy - Faulconbridge, James; Muzio, Daniel (Social Science Research Network, 2019)
Karl Polanyi is arguably one of the most significant economic sociologists. At first glance the links between Polanyi’s ideas about markets, society and institutions and strategy may not be obvious. However, there is a hereto unrecognised link between recent writing about institutions and strategy and Polanyi’s work. In this paper we, therefore, chart how, when recognised, these links reveal that Karl Polanyi’s work might provide new ways of thinking about strategy. Our over-riding claim is that Polanyi’s ideas reveal the importance of considering how strategies are defined, responded to, and ultimately rendered effective or ineffective in ways that are determined by relationships between markets, the state and society. It is thus crucial to understand strategy as embedded, this implying consideration of a strategy’s legitimacy in economy and society as an instituted process at any particular place and time. This also implies wider political questions about strategy in society and the extent to which strategists need to be aware of the ‘double movement’ Polanyi discusses and ensure strategies serve the interests of society as well as those of the market. KM: from forthcoming book "Critical perspectives on Accounting"
Keywords: double movement; embeddedness; professional services; strategy

How to conceptualize an alternative to platform capitalism according to the re-embedding process of K. Polanyi ? [Comment penser l'alternative au capitalisme de plateforme dans une logique de réencastrement polanyien ?] - Aufrère, Laura; Eynaud, Philippe; Maurel, Lionel; Vercher-Chaptal, Corinne (CEPN Working Papers, 2020)
The article considers alternatives to platform capitalism in a logic of Polanyian re-embedding. Stemming from case studies in the car-pooling, delivery and hosting sectors, the results uncover hybrid business models in which the market principle is used in the service of reciprocal logic. Rejecting the formal algorithmic rationality of capitalist platforms, the alternatives seek to align individual and collective behavior with values of solidarity and goals of general interest. They are experimenting with original methods of scaling up, based on the federation of communities, respectful of their anchoring in the substantive economy. The results make it possible to think of complementarities between different forms of embedding likely to be played out on several scales, and open perspectives for rethinking public policies vis-à-vis the experiments of the solidarity economy and the commons.
Keywords: coopérativisme de plateforme; decommodification; digital platforms; démar- chandisation; plateformes numériques; platform cooperativism; re-embedding; reciprocity; ré-encastrement; réciprocité; substantive economy; économie substantive